Effects of Exogenous and Autocrine Growth Hormone (hGH) on Prostate Cancer Cell Function - Nakonechnaya, Alena O. (East Carolina University, 2012)
Human growth hormone (hGH) is a major product of the anterior pituitary. In addition to its endocrine activities, hGH overexpression in extra-pituitary tissues has been correlated with the oncogenic behavior of these tissues, where it has been shown to function in an autocrine manner. hGH and its receptor (hGHR) have been shown to be expressed in prostate cancer (PCa) cells. Our preliminary work showed that expression of hGH and hGHR mRNA was elevated in PCa cell lines compared to normal prostate-derived epithelial cell lines, suggesting hypersensitivity of these cells to exogenous hGH, or establishment of autocrine signaling. Addressing these questions showed that PCa cells are sensitive to physiological concentrations of hGH, which can increase cell proliferation depending on the cell line. As shown in LNCaP cells, exogenous hGH increased DNA synthesis, whereas endogenous autocrine hGH resulted in decreased DNA synthesis and increased apoptosis. Investigation of the hGH signaling mechanisms in LNCaP cells revealed that autocrine hGH affected hGHR trafficking, resulting in the sequestering of hGHR inside the cell, likely in the Golgi apparatus and endoplasmic reticulum in the contrast with exogenous hGH which activated canonical signaling pathways. However, both exogenous and endogenous hGH increased LNCaP cell motility. This effect was accompanied by increased actin polymerization, which indicates a potential direct action of hGH signaling on the motility mechanism in PCa cells. Investigation of the molecular mechanisms of hGH-N gene activation in LNCaP cells compared to rat somatotropes and normal prostate epithelial cells revealed multiple cis activities in the 5'-flanking hGH-N promoter and corresponding DNA-binding activities were observed in PCa cells that were absent in normal prostate-derived cell lines. This suggests that hGH-N expression in LNCaP cells may be differentially regulated compared to normal prostate epithelium and pituitary somatotropes. Taken together, these studies indicate a hGH-N transcriptional activation mechanism associated with prostate cancer cells, and the responsiveness of prostate cancer cells to hGH. However, these results also suggest a distinction between the effects of endocrine and autocrine hGH, which may be due to the unique effect of autocrine hGH on hGHR trafficking.
Keywords: Chemistry, Biochemistry; Biology, Molecular; Exogenous vs. Autocrine; Growth hormone; Prostate--Cancer; Molecular biology; Biochemistry; Prostatic Neoplasms; Human Growth Hormone; Gene Expression Profiling--methods